Análise do desempenho de obras de pequeno porte na aplicação da filosofia Lean Construction: estudo multicaso na cidade de Pau dos Ferros/RN - Costa, Gustavo Ferreira (Universidade Federal Rural do Semi-Árido, 2017)
Lean Construction is characterized by the reduction of waste and the integration of production processes. Regarding to this, the present study aims to evaluate the development of activities in small constructions, located in Pau dos Ferros - RN, based on the feasibility analysis and the level of use of lean construction principles. The main purpose is to suggest improvements in their execution and, therefore, to identify the benefits that the application of the lean construction could provide to the development of the work. Accordingly, a bibliographical survey and on-site visits were carried out in six constructions, enabling the application of the lean construction checklist. From the data treatment, the Individual Principles Indexes (IPI) and the Lean Construction Index (LCI) were obtained. It was evidenced that the reality of the studied constructions does not match what is proposed in the concept of lean construction, considering a great deficit in the application of the principles that guide this productive model, since all the constructions were framed in level D, the lowest level among those presented in the Hofacker Table. This factor is due to the waste of materials and excessive generation of waste, as well as the lack of actions that would make it possible to renew and improve the development of daily activities. In view of this reality, it is concluded that the practical application of the principles of lean construction presents great potential to improve the management and integration of the construction activities as a whole, promoting a better performance and economic profitability to the constructions.
Keywords: Lean construction; Índice de Construção Enxuta; Obras de pequeno porte; Lean Construction; Lean Construction Index; Small Size Construction; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA